A música no trabalho pedagógico com a criança com transtorno do espectro autista - Souza, Júlia Braga Rodolfo de (Universidade Federal de São Carlos, 2022)
The work addresses the theme of music in the life of the autistic child, having as a principle the child as a subject of rights, bearer of history, capable of multiple relationships, affected by culture and producer of its own cultural forms, who plays, interacts and researches in contexts of which he or she is a part. This point of view considers that all children and their multiple childhoods have an equal right to exist and live in a pleasant way. The objective of the research is to investigate whether music is able to assist in the pedagogical development of children with Autism Spectrum Disorder (ASD), adopting the notion that the child is not dissociated from music, one of the expressive languages that constitutes his/her daily experiences, not just at school. It was found that ASD children have the right to music at school as art and play and, for that, there is a need for deeper teacher preparation on autism and on music education for the construction of a creative and democratic Early Childhood Education.
Music in pedagogical work with children with autism spectrum disorder
Keywords: Música; Music; Criança; Child; Transtorno do espectro autista; Autism spectrum disorder; Educação Infantil; Early childhood education; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO